Analisis Faktor-Faktor yang Mempengaruhi Kebijakan Hutang pada Perusahaan Jasa yang Listing di BEI Tahun 2013-2015 - Dedi Putra; Lilik Ramadhani (Jurnal Akuntansi dan Keuangan, 2017)
The objective of this study was to empirically examine the Factors Affecting Debt Policy in The Services Company in the Indonesian Stock Exchange in the period of 2013 - 2015. The sample was collected using purposive sampling method, acquired 18 service companies listed in the Indonesian Stock Exchange. The data analysis method used linear regression analysis with 95% confidence level. The result indicated that the managerial ownership, the institutional ownership and the foreign ownership had a significant negative effect on the debt policy. The company's growth and the dividend policy did not have a significant positive effect on debt policy. The public ownership and the profitability had a significant negative effect on the debt policy, and the asset structure a significant positive effect on the debt policy.